Effectiveness Assessment of Brand Microblog Marketing Communication under Trapezoidal Fuzzy Neutrosophic Sets - Yao Zhou (Neutrosophic Sets and Systems)
Brand communication tactics have changed to take use of new media channels, especially microblogging, in the age of digital transformation. It is now crucial to assess the success of brand microblog marketing communication to comprehend customer involvement, message distribution, and brand positioning. With an emphasis on elements like audience engagement, material quality, and brand perception, this study investigates the standards for evaluating the effectiveness of microblog marketing initiatives. The study offers insights into the tactics that are most important for effective communication using a systematic evaluation approach. We use multi-criteria decision making (MCDM) to deal with different criteria. We use the Trapezoidal Fuzzy Neutrosophic Sets (TFNSs) to deal with uncertainty information. The results are meant to help businesses maximize their microblog presence for more effective marketing.